Novel clinical algorithm for hypothalamic obesity in youth with brain tumours and factors associated with excess weight gain. Issue 7 (27th February 2022) - Rydin, Amy A.; Severn, Cameron; Pyle, Laura; Dorris, Kathleen; Chambers, Christina; Stiller, Debra; Hankinson, Todd C.; Inge, Thomas; Haemer, Matthew A.; Mirsky, David M.; Moore, Jaime; Kelsey, Megan M.
Summary: Background: A standardized approach for identifying and treating hypothalamic obesity (HO) in children with hypothalamic tumours is lacking. Objectives: To describe children with hypothalamic tumours at risk for obesity, assess outcomes of a novel HO clinical algorithm, and identify factors associated with weight gain. Methods: Retrospective analysis of youth with hypothalamic and suprasellar tumours, seen at a paediatric tertiary care centre from 2010 to 2020. Results: The study cohort ( n  = 130, 50% female, median age at diagnosis 5 [range 0–17]y) had a median duration of follow up of 5 (0.03–17)y. At last recorded body mass index (BMI) measurement, 34% had obesity, including 17% with severe obesity. Median onset of overweight and obesity after diagnosis was 6.2 (0.3–134) and 8.9 (0.7–65) months, respectively. After algorithm implementation ( n  = 13), the proportion that had an early dietitian visit (within 6 months) increased from 36% to 54%, ( p  = 0.498) and weight management referrals increased from 51% to 83% ( p  = 0.286). Higher BMI z‐score at diagnosis was associated with overweight and obesity development ( p  < 0.001). Conclusion: Patients with hypothalamic tumours commonly develop obesity. Use of a clinical algorithm may expedite recognition of HO. Further research is needed to identify predictors of weight gain and to develop effective treatment.